1983
DOI: 10.1136/pgmj.59.697.707
|View full text |Cite
|
Sign up to set email alerts
|

Renal lesions in leprosy amongst north Indian patients

Abstract: SummarySixty consecutive patients with leprosy were investigated for renal involvement. Clinically overt renal disease was present in 4 patients; 3 presented with a nephrotic state and one patient with progressive renal failure. Urinalysis showed daily protein loss ranging from 0-4 to 8-9 g in 8 patients and microscopic haematuriain 4 cases. Flevated levelsofblood urea and creatinine were seen only in one patient with diffuse proliferative glomerulonephritis. Of the 36 patients in whom distal tubular functions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…[18] Proteinuria has been described in several studies and its prevalence varies from 2.1 to 68%, and it is also more frequent in the multibacillary forms. [15,19,20,21,22] The prevalence of renal involvement in our study is comparable to previous studies. Experimental studies have suggested that reticuloendothelial system gets involved early in the course of the disease.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…[18] Proteinuria has been described in several studies and its prevalence varies from 2.1 to 68%, and it is also more frequent in the multibacillary forms. [15,19,20,21,22] The prevalence of renal involvement in our study is comparable to previous studies. Experimental studies have suggested that reticuloendothelial system gets involved early in the course of the disease.…”
Section: Discussionsupporting
confidence: 81%
“…[14] Microscopic hematuria is found in 12-16% of cases, which is higher than what is found in the general population (0.5-2%). [15,16,17] This complication can disappear after a few months of specific treatment. [18] Proteinuria has been described in several studies and its prevalence varies from 2.1 to 68%, and it is also more frequent in the multibacillary forms.…”
Section: Discussionmentioning
confidence: 99%
“…Even though many biopsy and autopsy studies have since then been carried out, the exact pathogenesis of those renal lesions is still uncertain [4]. They become important if one considers that chronic renal failure, attributed in most cases to amyloidosis, is the main cause of death in leprosy [2,5].…”
Section: Introductionmentioning
confidence: 99%
“…These uncommon cases were presented as case reports due to their rarity 31 . Glomerulonephritis seems to be the most common type of nephropathy in leprosy, accompanied by hematuria and increased proteinuria, especially in multibacillary forms 32,33 . The exact mechanism leading to the development of glomerulopathy is not completely understood.…”
Section: Leprosymentioning
confidence: 99%